The Widespread Use of Foreign Word on Artificial Element Topographical Name in the District and the City of Bogor - Asadi, Asadi (Jurnal Bina Praja, 2016)
Lately, found many artificial elements topographical names for the names of residents, apartments, and modern markets in a foreign language, especially English. Referring to the legislation governing the use of topographical names, then the provision of topographical names must use Indonesian or local languages. Unfortunately, the obligation to use Indonesian in the provision of topographical names has not been properly socialized and the violation is not accompanied by legal sanctions. This paper examines the issues that are currently going on and developed in society towards topographical naming of artificial elements and the factors that cause the use of foreign names. The method used in this study is a descriptive qualitative method. The result of the study concluded that the English naming for the topographical name of artificial elements due to the influence of globalization, marketing strategy by housing developers, legislation that has not been properly socialized, and the absence of sanctions against violations of the obligation to use Indonesian in the topographical naming of artificial elements. It is expected that this paper can provide awareness to all parties to use Indonesian in the topographical naming of the artificial elements.